Human caregivers perceive racial bias in their pet dogs. (September 2019) - Hawkins, Carlee Beth; Vandiver, Alexia Jo
Is there any empirical support for the popular stereotype that dogs are racist? As an initial inquiry into this question, we investigated whether human caregivers perceive racial bias in the behavior of their pet dogs. In 2 studies, caretakers completed explicit and implicit measures of racial preference and reported their dogs' behavior toward White and Black people. White caretakers reported that their dogs displayed more positive behaviors toward White than Black people, and these reports of dog behaviors were significantly correlated with caretakers' own explicit and implicit racial preferences. Increased interracial contact was associated with less reported pro-White dog behavior. Humans perceive racial biases in those around us, including our pets.